Aquaculture and fisheries biotechnology : - Dunham, Rex A. (CABI Publishing, 2004)
The genetic improvement of fish for aquaculture and related fisheries is a field of research that has seen immense advances in recent years. Yet there is no book which provides an accessible overview of the subject. This book aims to fill this gap and will be suitable for advanced students and researchers in animal genetics, fish biology and aquaculture.